A Daily Examination of African American Adolescents' Racial Discrimination, Parental Racial Socialization, and Psychological Affect. Issue 6 (7th August 2020) - Cheeks, Bridget L.; Chavous, Tabbye M.; Sellers, Robert M.
Abstract : This study examined 164 African American adolescents' ( M age  = 15) daily reports of racial discrimination and parental racial socialization over 21 days. The study examined same‐day and previous‐day associations of adolescents' discrimination and socialization experiences with their positive and negative psychological affect. It further explored whether racial socialization messages buffered discrimination's effects on affect when messages were received during the same day and on the day prior to discrimination. Findings indicated the deleterious effect of racial discrimination (associated with more negative affect) and highlighted the importance of examining youth's short‐term coping in critical developmental years. Findings also showed how messages promote positive youth emotions. However, daily moderating associations differed from prior survey studies, suggesting the importance of examining short‐term processes.